1996
DOI: 10.1148/radiology.198.1.8539389
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal aortic aneurysms: preliminary technical and clinical results with transfemoral placement of endovascular self-expanding stent-grafts.

Abstract: Exclusion of AAA from circulation was feasible, safe, and clinically effective with the new stent-graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
62
0
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(63 citation statements)
references
References 0 publications
0
62
0
1
Order By: Relevance
“…Initial technical success may be defined as successful introduction of the stent-graft system and exclusion of the aneurysm sac at the end of the procedure. Success rates of 89%-100% have been reported by various groups using different stent-graft systems [5,7,8]. Our own initial technical success rate for bifurcated stentgrafts is 95% [9].…”
mentioning
confidence: 76%
“…Initial technical success may be defined as successful introduction of the stent-graft system and exclusion of the aneurysm sac at the end of the procedure. Success rates of 89%-100% have been reported by various groups using different stent-graft systems [5,7,8]. Our own initial technical success rate for bifurcated stentgrafts is 95% [9].…”
mentioning
confidence: 76%
“…The spiral CT studies were performed with a Toshiba Xpress/XS (Toshiba, Tokyo, Japan) imager, with a contrast agent, Omnipaque 300 mg I/ml (Nycomed, Oslo, Norway), in the in vivo studies. CT and CT angiography are the most commonly used methods for follow-up of endovascular treatment of AAA (4,7,13), and spiral CT is included in our follow-up after such treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that this procedure may be a less invasive alternative to conventional surgery (3)(4)(5). However, procedure-related complications that may require secondary interventions necessitate a regular follow-up (6 -8).…”
mentioning
confidence: 99%
“…Medium-term results have been encouraging in cases fit for this treatment, [2][3][4][5][6][7][8][9][10][11][12][13][14] and complication rates have been moderate by comparison with standard surgery. 7,[15][16][17][18][19][20][21][22][23][24][25][26] Effective endovascular treatment results in a significant pressure reduction 27 and a shrinkage of the excluded aneurysm.…”
mentioning
confidence: 99%